Mathematical modelling of respiration control system - Švitra, Donatas; Vilkytė, Ramunė (Lietuvos matematikos rinkinys, 2012)
In this article the authors performed respiratory system mathematical model, described by two differential equations with one delay argument linear, nonlinear and numeric analyses. Linear analysis was performed D-segmentation method. A stable periodic solution application on bifurcation theory was constructing in the nonlinear analysis. In the numeric analysis using Runge–Kutta IV series method, numerical solutions have been constructing to the pathologic Cheyne–Stokes case.
Keywords: periodic respiration; bifurcation theory; D-segmentation method